SMART OPTIMAL REPLACEMENT FOR HOSTEL MAINTENANCE MANAGEMENT BASED ON INCOMPLETE DATA (Journal of Engineering and Health Sciences, 2022)
The best times at which replacements action for building maintenance to execute need to be determined in order to minimize the total downtime and cost per unit time. The failure data is gathered during a selected period of time and if not sufficient, a subjective survey form and bootstrapping methods are used to support the incomplete information. The frequency of maintenance is identified by developing the intelligent optimal replacement model based on the cost and downtime value. The result shows that with the model maintenance staffs have additional features to support them in making maintenance decision.